Lyndsey STONEBRIDGE. 2020. Writing and Righting: Literature in the Age of Human Rights. Oxford: Oxford University Press, 176 pp. ISBN 9780198814054 (Analele Universității din București. Științe Politice, 2024)
The rhetorically scintillating homophonic pair within the title certainly catches the reader’s attention to one of the still very few extensive works that explore the role that literature has played in the history of human rights. Both writing and righting rely on creativity and comprehension to render human values understandable and visible. But in this collection of essays that continues the line of argumentation already developed in The Judicial Imagination: Writing After Nuremberg (Stonebridge 2011) and Placeless People: Writing, Rights and Refugees (Stonebridge 2018), Lyndsey Stonebridge goes beyond the  assumption that literary education brings obvious humanizing benefits.